Marital Rape and its Social Demographic Factors Associated with Gynecological Problems in Kirtipur - Shakya, T M; Dangal, G; Poudyal, A K (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study aimed to find association of marital rape with gynecological problems and socio-demographic factors, which helped to explore possible underlying issues and to provide appropriate services to the women. Methods: A cross sectional quantitative study was carried out. Three hundred sixty two married women who came to the health care centres of Public Health Concern Trust (phect-NEPAL) for any kind of health services were enrolled for the study. Data was collected through semi structured interview questionnaire. Bivariate analysis and multiple binary logistic regression analysis were applied to identify the factors associated gynecological problems and marital rape. Results: The study revealed that out of 362 women, 194 (53.6%) experienced marital rape either everyday or sometime. Out of 362 women, 48.6% (194) were suffered from gynecological problems. Women who had undergone rape had 2.32 times more likely to experience gynecological problems than those who did not (OR 2.3, 95% CI 1.52-3.55). Marital rape was found statistical significantly associated (p-value < 0.05) with economic condition, interspousal communication, and difference among interspousal sexual desire, husband’s violent nature, husband's dominant attitude, husband’s alcohol intake and gynecological problem. Conclusions: Marital rape was associated with existence of gynecological problem in the wife. Therefore, women with gynecological problems should also be explored for marital rape and counseling and service should be provided. DOI: http://dx.doi.org/10.3126/njog.v9i2.11767